O‘ZBEK TILIDA NOM YARATISH KOMUNIKATIV ALOQA VOSITASI SIFATIDA - Suyunov, Xusniddin (FILOLOGIYA UFQLARI JURNALI, 2023)
This article talks about the fact that creating a name is a unique process, subject to certain requirements, rules and linguistic criteria, and a new name in each language is created using special language tools based on the internal capabilities of this language. . Also, the names are different according to what kind of object they are naming, including production, trade, household service objects, products, and the names given to their brand (brand) are different in terms of having a specific purpose. distinguished from names. Ideas have been put forward that the activity of creating names for such objects and manufactured products is called naming in marketing.